Blocking IL-25 signalling protects against gut inflammation in a type-2 model of colitis by suppressing nuocyte and NKT derived IL-13 - Camelo, Ana (Springer Japan, 2012)
BACKGROUND: Interleukin-25 (IL-25) is a potent activator of type-2 immune responses. Mucosal inflammation in ulcerative colitis is driven by type-2 cytokines. We have previously shown that a neutralizing anti-IL-25 antibody abrogated airways hyperreactivity in an experimental model of lung allergy. Therefore, we asked whether blocking IL-25 via neutralizing antibodies against the ligand or its receptor IL-17BR could protect against inflammation in an oxazolone-induced mouse model of colitis. METHODS: Neutralizing antibodies to IL-25 or IL-17BR were administered to mice with oxazolone-induced colitis, a model of ulcerative colitis. The disease onset was evaluated by weight loss and degree of colon ulceration. Also, lamina propria and mesenteric lymph node (MLN) infiltrates were assessed for mucosal inflammation and cultured in vitro to determine cytokine production. RESULTS: We found that in oxazolone colitis IL-25 production derives from intestinal epithelial cells and that IL-17BR(+) IL-13-producing natural killer T (NKT) cells and nuocytes drive the intestinal inflammation. Blocking IL-25 signalling considerably improved the clinical aspects of the disease, including weight loss and colon ulceration, and resulted in fewer nuocytes and NKT cells infiltrating the mucosa. The improved pathology correlated with a decrease in IL-13 production by lamina propria cells, a decrease in the production of other type-2 cytokines by MLN cells, and a decrease in blood eosinophilia and IgE. CONCLUSION: IL-25 plays a pro-inflammatory role in the oxazolone colitis model, and neutralizing antibodies to IL-25 or IL-17BR can slow the ongoing inflammation in this disease. Because this model mimics aspects of human ulcerative colitis, these antibodies may represent potential therapeutics for reducing gut inflammation in patients.